EVALUATION OF VARIOUS GRAFT MATERIALS IN MYRINGOPLASTY - DR T V V VINAY KUMAR (International Journal of Pharma and Bio Sciences, 2015)
The objective of this study was to compare the effect of various graft materials influencing the outcome of myringoplasty and other factors like age of the patient, size of the perforation, duration of discharge with that of previous studies.We studied a series of 60 patients of chronic suppurative otitis media tubotympanic disease over period of 2 years at the department of ENT , Navodaya Medical College Hospital.A detailed proforma was filled for each patient. Audiological evaluation(pure tone audiometry) was done preoperatively, 3months and 6months after surgery and the results tabulated.Statistical comparisons were performed using the Students ‘t’test,Chi-square test,and Anova test. Out of 60 patients there were 31 males and 29 females with a mean age of 27.4 years. In our study in the age group of 10-40 years the audiological benefit in speech frequency was found to be 11.05 dB and in high frequency it was found to be 7.79 dB. In patients aged over 40 years the audiological benefit was 10.83 d B in the speech frequency and 8.5 d B in the high frequency.Statistically patients with duration of ear discharge more than 11 years and less than 20 years showed more audiological benefit.In our study 10 patients had small perforations of the tympanic membrane, 20 patients had medium perforations and 30 patients had large perforations .The audiological benefit seen in the speech frequency for patients with small perforations was 4.1 whereas in the high frequency no audiological benefit was observed. In patients with medium perforation the audiological benefit in speech frequency was 9.7 and for high frequency it was 7.5. in patients with large perforations the audiological benefit was 14.2 in speech frequency and 11.03 in high frequency.In 34 patients temporalis fascia was used as the graft material, in 13 patients tragal perichondrium was used and in 13 patients composite cartilage was used as the graft material for myringoplasty. In our study, of 93.3% cases showed audiological improvement in the speech frequency range postoperatively. There was no change in the hearing level in 5.1% of cases and worsening of hearing seen in 1.6% of cases in the speech frequencies. Maximum improvement was seen in temporalis fascia group compared to cartilage and tragal perichondrium and out of the three grafts least benefit was seen with cartilage graft. However these differences were not statistically significant.Age of the patient, size of the perforation and the type of graft used were found to have an effect on the final outcome of surgery.